Cyanobacteria as a Source for Novel Anti-Leukemic Compounds - Humisto, Anu; Herfindal, Lars; Jokela, Jouni; Karkman, Antti; Bjørnstad, Ronja; R. Choudhury, Romi; Sivonen, Kaarina (Current Pharmaceutical Biotechnology, 2016)
Cyanobacteria are an inspiring source of bioactive secondary metabolites. These bioactive agents are a diverse group of compounds which are varying in their bioactive targets, the mechanisms of action, and chemical structures. Cyanobacteria from various environments, especially marine benthic cyanobacteria, are found to be rich sources for the search for novel bioactive compounds. Several compounds with anticancer activities have been discovered from cyanobacteria and some of these have succeeded to enter the clinical trials. Varying anticancer agents are needed to overcome increasing challenges in cancer treatments. Different search methods are used to reveal anticancer compounds from natural products, but cell based methods are the most common. Cyanobacterial bioactive compounds as agents against acute myeloid leukemia are not well studied. Here we examined our new results combined with previous studies of anti-leukemic compounds from cyanobacteria with emphasis to reveal common features in strains producing such activity. We report that cyanobacteria harbor specific anti-leukemic compounds since several studied strains induced apoptosis against AML cells but were inactive against non-malignant cells like hepatocytes. We noted that particularly benthic strains from the Baltic Sea, such as Anabaena sp., were especially potential AML apoptosis inducers. Taken together, this review and re-analysis of data demonstrates the power of maintaining large culture collections for the search for novel bioactivities, and also how anti-AML activity in cyanobacteria can be revealed by relatively simple and low-cost assays.
Keywords: bioactive compounds